Learning to be old : gender, culture, and aging - Cruikshank, Margaret (Lanham : Rowman & Littlefield, 2013)
This work examines what it means to grow old in America today. The book questions social myths and fears about aging, sickness, and the other social roles of the elderly, the over medicalization of many older people, and ageism. Here the author proposes alternatives to the ways aging is usually understood in both popular culture and mainstream gerontology. She does not propose the ideas of "successful aging" or "productive aging," but more the idea of "learning" how to age. Featuring new research and analysis, the third edition of this text demonstrates, more thoroughly than the previous editions, that aging is socially constructed. The book focuses on the differences in aging for women and men, as well as for people in different socioeconomic groups. The author is able to put aging in a broad context that not only focuses on how aging affects women but men, as well. Key updates in the third edition include changes in the health care system, changes in how long older Americans are working especially given the impact of the recession, and new material on the brain and mind-body interconnections. The author challenges conventional ideas about aging, and brings forth some new ideas surrounding aging in America today.
Cultural myths and aging -- Fear of an aging population -- Sickness and other social roles of old people -- Overmedicating old Americans -- Healthy physical aging -- The politics of healthy aging -- Class, ethnicity, sexual orientation, and gender -- Ageism -- Countercultural gerontology -- A feminist's view of gerontology and women's aging -- The paradoxes of aging.
Includes bibliographical references and index.
Keywords: Aging -- Psychological aspects; Older people -- United States